Um molde para a prática de gestão do conhecimento sustentável, adaptável ao perfil das organizações: estudo de caso de um projeto para o fortalecimento do arranjo produtivo local de tecnologia da informação da Paraíba - Vilar, Rosangela Maria (2009)
Knowledge Management has become essential for organizations to ensure a better strategic position facing the reality of their surroundings. Organizations, especially the medium and large sizes, have solutions from various sources, with more facilities for the deployment of a KM practice. As for the small ones, they have yet to understand the challenges and opportunities of KM to improve their business processes and develop their Competitive Intelligence. This can be achieved through a strategic practice to provide sustainability to the KM activities, reducing the risk of rejection by the various actors to changes resulting from the implementation of this practice into the organization s body of work routines. This paper presents a flexible mould (metamodel) to aid the planning and implementation of an effective organizational KM, i.e., a tool for designing a KM practice adaptable to the organization profile, whichever its size and its rate of absorption of the designed practice. From an instance of strategic planning and evaluation of the voice from organization actors is built a model, through the intantiation of the mould for each single case, for the design of a KM practice liable to strict management based on Administration Theory sub-functions (planning, organization, direction and control), allowing managers of an organization (the strategic level actors) to display its weaknesses and identify its potentialities in relation to the KM practice. In keeping with the profile of the various actors in the organization, the mould can be instantiated minimizing the rejection to the additional work routines and changes in the actors new way of working, due to the implementation of the new practice. To demonstrate the mould and exemplify its instatiation, the case of a virtual organization, Farol Digital a project for strengthning the Paraiba State ICT Cluster, is analysed along with the artifacts produced by the instantiation of this particular case.